Kecemasan terhadap Komputer di Era E-Government - Arief Fahmie (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2003)
Regional government in many Indonesian provinces are currently applying information technology in order to better serve the people through the e-government program. E-government is an internet based information management system to assist the public in accessing, searching and recording public information from the government. This paper examines the consequences which might be faced by government employees in facing a change of the work technology. Studies showed that one out of the many issues related to use of computer technology is computer anxiety. It is found that high anxiety related to computer technology occur as a form of techno-stress and is associated with psychological symtoms, known as computer anxiety. High computer anxiety is thought to be related to negative work attitudes. Thus, internal and external factors related to computer anxiety need to be examined in order for the government organizations to deal with computer anxiety, both as prevention and intervention, more effectively.Key Words : E-government, Computer anxiety, Prevention, Intervention.